Neutrophil-lymphocyte ratio, red cell distribution width and mean platelet volume as practical markers in febrile seizure classification - Pelin Balikoğlu; Ayse Oflu; Ayşegül Bükülmez (Sociedade de Pediatria de São Paulo, 2023)
ABSTRACT Objective: To examine the neutrophil-lymphocyte ratio, red cell distribution width and mean platelet volume in patients with febrile seizure and to determine their role in febrile seizure classification. Methods: This was a retrospective hospital-based study conducted among patients aged 5 to 72 months admitted with febrile seizure. Children who had febrile seizures due to upper respiratory tract infection were included in the study. The children were divided into two groups: simple febrile seizures and complex febrile seizures. Patients with a history of febrile status epilepticus, previous convulsions, use of antiepileptic or other chronic drugs, foci of infection other than the upper respiratory tract infection, abnormal biochemical parameters, and chronic mental or physical disease were excluded from the study. Clinical and laboratory findings of the patients were obtained from digital medical records. Results: The records of 112 febrile seizure patients were reviewed, and 89 were grouped as simple and 23 as complex febrile seizures. Although there was no statistically significant difference between the two groups in terms of the mean red cell distribution width values (p=0.703), neutrophil-lymphocyte ratio and mean platelet volume were significantly higher in patients with complex febrile seizures (p=0.034, p=0.037; respectively). Conclusions: This study showed that neutrophil-lymphocyte ratio and mean platelet volume could be practical and inexpensive clinical markers for febrile seizure classification. A similar result could not be reached for red cell distribution width in this study. These findings should be supported by multicenter studies with large samples.